PENGARUH PENAMBAHAN TEPUNG KACANG MERAH (Phaseolus Vulgaris Latau) TERHADAP DAYA TERIMA STICK IKAN CAKALANG (Katsuwonus Pelamis) - Lia Limbong; Maria F.Vinsensia D P Kewa Niron (Kupang Journal of Food and Nutrition Research, 2026)
Protein Energy Malnutrition (PEM) remains a major nutritional issue among toddlers and significantly contributes to Protein-Energy Malnutrition (PEM) remains a major nutritional problem among infants and young children and contributes to high child mortality rates. Data from the World Health Organization (WHO) indicates that approximately 54% of child deaths are caused by Protein-Energy Malnutrition. One preventive measure involves utilizing local foods, such as skipjack tuna—which is high in animal protein—and red beans as a source of plant-based protein, by processing them into stick-shaped products. These stick products are designed as snacks weighing 50 grams per serving to help meet the daily nutritional needs of healthy infants and toddlers, supplementing their daily nutritional requirements beyond main meals. The objective of this study is to determine the effect of adding red bean flour on the organoleptic acceptability (color, aroma, taste, and texture) as well as the nutritional value of skipjack tuna sticks. An experimental research method was used with three treatments: the addition of 42% red bean flour (L1), 47% (L2), and 52% (L3). Organoleptic testing was conducted by panelists using the Kruskal-Wallis test, while nutritional value analysis was based on TKPI 2020. The results of the organoleptic test showed no significant differences among the treatments (p > 0.05), but all formulations fell into the “like” category (scores of 3.6–4.0). In terms of color, L1 and L2 were the most preferred; for aroma and texture, L2 and L3 were preferred; while L2 received the highest score for taste. Nutritional analysis showed an increase in energy and protein as the proportion of red beans increased, with the highest values in L3 (Energy 2,413.4 kcal; protein 93.8 g; fat 97.75 g; carbohydrates 293.25 g). Based on the nutritional analysis results, the recommended formulation is skipjack fish sticks with 52% red bean flour added (L3). As a snack, this product has higher energy and protein levels than the other treatments, which can help meet the energy and protein needs of undernourished toddlers. Further research is needed regarding the content or analysis of other micronutrients in the fish stick formulation.